DETERMINANTS OF REMITTANCES SENT TO HOME REGIONS BY MIGRANT WORKERS IN DENPASAR CITY - Ni Wayan Viona Pradnya Sayoga; Anak Agung Istri Ngurah Marhaeni (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The limitations faced by home regions in fulfilling basic living needs encourage people to migrate to more promising areas in pursuit of decent income and to send remittances as economic support for families in their places of origin. This study aims to analyze: (1) the effect of education level, length of employment, employment status, and number of dependents on the income of migrant workers; (2) the effect of education level, length of employment, employment status, number of dependents, and income on remittances sent to the home region by migrant workers; and (3) the indirect effects of education level, length of employment, employment status, and number of dependents on remittances through income among migrant workers in Denpasar City. This associative quantitative research involved 100 migrant workers in Denpasar. Data were collected through observation and interviews and analyzed using descriptive statistics, path analysis, and the Sobel test. The findings reveal that: (1) education level, length of employment, and number of dependents have a positive and significant direct effect on the income of migrant workers in Denpasar City. Migrants working in the formal sector earn higher incomes; (2) education level, length of employment, number of dependents, and income have a positive and significant direct effect on remittances sent by migrant workers in Denpasar City. Migrants employed in the formal sector send higher remittances; and (3) education level, length of employment, and number of dependents have an indirect effect on remittances through income.